ENHANCING NETWORK EFFICIENCY: A COMPARATIVE STUDY OF REAL-TIME PERFORMANCE WITH STRATEGIC RELAY NODE PLACEMENT - Thompson, David; Lee , Sarah (Ayden Journal of Agriculture and Allied Studies, 2024)
Wireless Sensor Networks (WSNs) have gained substantial attention and widespread adoption across industries, agriculture, smart homes, and other domains due to their potential capabilities [1-4]. In WSNs, spatially distributed Sensor Nodes (SNs) collect data from various environments, with Sink Nodes (SNs) serving as data aggregators. These networks often rely on battery-powered sensors, allowing portability but constraining power supply and communication range [5-6]. To enhance network longevity and scalability, additional nodes called Relay Nodes (RNs) are introduced, which possess ample power and suitable communication ranges to forward data between SNs and sink nodes [7]. Minimizing deployment costs while considering network delay, connectivity, lifetime, and reliability constraints constitutes the Relay Node Placement (RNP) Problem, recognized as NP-hard. The Delay Constrained RNP (DCRNP) problem is a crucial subset of RNP, particularly relevant in industrial automation and smart grid domains [9-10]. Real-time data from precision instruments (acting as SNs) must be promptly and reliably transmitted to control centers (serving as sink nodes) in applications such as industrial automation [10]. Existing RNP approaches focus on reliability and fairness without prioritizing real-time performance, rendering them unsuitable for such scenarios. The paper primarily addresses response delay, often equated with hop count, as the criterion for delay evaluation.